PENGEMBANGAN MEDIA WAYANG KERTAS PADA PEMBELAJARAN BAHASA JAWA - Ngajijah, Ngafifatul; Azizah, Wida Nurul; Mukhlasin, Ahmad (Journal of Professional Elementary Education, 2024)
This research aims to produce learning media products that are suitable for use for learning in MI (Madrasah Ibtidaiyah) or SD (Primary School). This research is development research or Research and Development to obtain the results of certain products used during research which is a needs analysis to test the validity of the product so that it can function for students in MI or elementary school and the wider community. Before being tested on MI children, the media developed was validated by media experts and material experts. The instrument used to collect data was a media expert and material expert feasibility test questionnaire. This research produces learning media in the form of paper puppets for learning Javanese. Meanwhile, the feasibility of this product is proven by the validation results of media experts getting an average percentage of 78.5%, the feasibility test of material experts getting an average percentage of 82%. Based on the trial at school I with an average percentage of 86.2% in the very feasible category and the trial at school II with an average percentage of 94.1% in the very feasible category. Based on the results of implementation tests which show that the product developed in the category is very feasible so that over all it is suitable for use as a learning medium